Hubungan Pengetahuan Gizi dan Keamanan Pangan Dengan Konsumsi Mie Instan Pada Santriwati SMA Pondok Pesantren Asy-Syarifah Mranggen Demak - Aini Mubarokah; Agus Sartono; Joko Teguh Isworo (Jurnal Gizi, 2014)
Adolescence is a period that has not fully matured, both physical, cognitive and psychosocial. At this time the teens easily influenced by environment and lifestyle, one of which is the pattern of consumption, such as the consumption of instant noodles. Given the ongoing growth, adolescence have a higher nutritional needs, for optimal growth and development. Less consumption of both quality and quantity to provide health and nutrition is not balanced so it will show a variety of diseases, such as malnutrition (over nutrition/obesity or under nutrition), and food poisoning. Domain knowledge is very important in shaping a person`s behavior. A person`s level of nutritional knowledge may influence the in the relationship of nutrition and food safety knowledge with instant noodle consumtion of santriwati at boarding school Asy-Syarifah Mranggen Demak.The type of the study is descriptive analytic with the number of subjects are 45 people of santriwati at High School Boarding Schools Asy-Syarifah Mranggen Demak. The subjects are taken by stratified random sampling method from the total number of santriwati(80 people). For analysis the data, Spearman rank test with SPSS for Windows are used in this studi.The results showed that the 30 people (66,7%) of santriwati in the high school Asy-Syarifah Boarding School, have a middle category of knowledge level. The 25 people (55,6%) of santriwati have a high category of instant noodles consumption level. Statistical analysis showed that there is a negative relationship betwen knowledge of nutrition and food safety santriwati with instant noodle consumption (r = - 0.520 and p-value = 0.000).